Políticas inclusivas: desafios à prática e à identidade docente - Hüsken, Rosane Bom (2012)
The present work was based on elementary school teachers oral narratives working in the initial years at city public schools in Pelotas, who face in their practices the experience of inclusion of children with special needs. In this study, the challenges by which the teaching practice and identity are put into, due to the use of inclusive policies as a background, were problematized. Thus, the purpose of the present work was to investigate how elementary school teachers from city-run public schools in Pelotas experience their teaching practices with special students, analyzing how they understand and recontextualize, in their practice, the inclusive educational practices, identifying how the work with special students influences their teaching identities. In order to develop this study, I used as references the legal texts relevant to the research theme and the studies from Stuart Hall, on representations and identity; from Basil Bernstein, on recontextualization; from Stephen Ball, on educational policies and subjectivity; and from Antonio Nóvoa, on the teaching work. Also, the studies from MauriceTardif and Claude Lessard on teaching work and teaching knowledge. The empirical research showed that the practice of the teachers with the special students present unique characteristics due to each one s career time, and whose variations occur as a result of the understanding of how the teaching knowledge is acquired, as well as unclearness and the uncertainty of the pedagogical practice, showing at times, a contradictory movement between knowing and doing, highlighting how the policies may be decontextualized and recontextualized, mainly in the field of curriculum practices. They demonstrate that their teaching identities are in constant process of construction/deconstruction/reconstruction. Although the teachers are subject to pressures and contradictions, as along their narratives they did not demonstrate having understood the relation found between the innovations incorporated into the teaching activity, its intensification and the commitment of their time and subjectivities by the school context with the demands of recent educational policies, mainly the ones concerning school inclusion to special children. Neither they seemed to understand the relationship between these policies and the discourses that challenge the teaching activity. In the end, dealing with what is different or unusual leads to an afflicted teaching identity, subject to a never-ceasing search for safer ways and references, by which they can anchor with more meaning and significance their teaching identities